Anti-fatigue activity of Brassica rapa L. extract and correlation among biochemical changes in forced swimming mice. (June 2022) - Li, Zilin; Zhu, Hongkang; Hua, Hanyi; Liu, Chang; Cheng, Yuliang; Guo, Yahui; Du, Peng; Qian, He
Abstract: Brassica rapa L. is an edible and medical plant in China used for treating various diseases, especially in the Tibet region. In this study, the chemical constituents of Brassica rapa L. extract (BE) was clarified by UHPLC-MS and anti-fatigue ability of BE was assessed through the behavior test and weight-loaded forced swimming test in mice. Then we determined several biochemical parameters related to fatigue to explore possible reasons. Results indicate that BE could significantly enhance exercise performance in mice, and there was a significant improvement in both grip-strength and the time on rota-rods. Meanwhile, BE showed significant anti-fatigue effects by decreasing the blood lactic acid (BLA), blood urea nitrogen (BUN), and creatine kinase (CK) levels and increasing the lactate dehydrogenase (LDH) and malondialdehyde (MDA) levels. Increases in superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) were observed and reactive oxygen species (ROS) levels was regulated. Liver and muscle glycogen levels and adenosine triphosphate (ATP) levels were also significantly increased. Pearson correlation analysis indicates that fatigue-related indexes including metabolites and energy-related indexes were significantly correlated with antioxidant levels. In conclusion, BE possesses remarkable anti-fatigue activity, thereby shows great potential for improving exercise performance and alleviating physical fatigue and can be considered as a functional food supplement for further development. Graphical abstract: Image 1 Highlights: The chemical constituents of BE was clarified by UHPLC-MS. Anti-fatigue effect of Brassica rapa L. extract (BE) was evaluated in swimming mice. BE improves motor performance by regulating energy metabolism and oxidative stress. Pearson correlation analysis among fatigue-related biochemical changes was performed.